PELATIHAN PENINGKATAN PENJUALAN TENUN SEBAGAI KOMODITAS UTAMA DESA SEBAUK MELALUI PEMASARAN DIGITAL SYARIAH - Dewi Oktayani; Siti Suhana; Zakiatul Munawarah; Shinta Juliani; Salmilah Salmilah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This Community Service program aimed to enhance the sales of woven fabrics (tenun) as the primary commodity in Sebauk Village through the implementation of sharia-based digital marketing. The approach applied was the ABCD (Asset-Based Community Development) method, emphasizing the development of local community assets. The results showed that training and assistance in sharia-compliant digital marketing significantly improved the artisans’ knowledge and skills in online marketing. By utilizing Islamic value-based digital platforms, Sebauk woven products successfully reached wider markets. The program had a positive impact on the local economy and contributed to the preservation of cultural heritage.